One of the top technological universities in Malaysia - Irene, Wei Kiong Ting (2019)
Universiti Malaysia Pahang (UMP) ranked for three different subjects, viz. (i) Mechanical, Aeronautical and Manufacturing, (ii) Chemical Engineering, and (iii) Engineering and Technology, in the recently released QS World University Rankings by Subject 2019. The inclusion of the latter two subjects in QS subject tables marks two more additions than UMP did last year, indicating that UMP has become more prominent in the technical field of education. Furthermore, the rankings once again recognized UMP as the leader within the Malaysian Technical University Network (MTUN), which is made up of four technological universities in Malaysia, with only UMP earning a place in the subject table of Chemical Engineering.